OBSERVATIONS ON THE FOOD OF JUVENILES OF PSETTODES ERUMEI (BLOCH) - Devadoss, P; Pillai, P K Mahadevan (Indian Journal of Fisheries, 2011)
Juveniles of Psettodes erumei (Bloch) were observed in large numbers at Porto Novo during April - May 1972. Size frequency studies showed the dcaninance of only one group (60-6 4 nun) in the catches. ITie stomach contents consisted of only larval and post larval forms of other fishes such as Polymmus, sciaemds ThHssodes, Anchoviella^ and leiognatbids besides small prawns and squids.